The future past of tourism historical perspectives and future evolutions - McMahon-Beattie, Una; Yeoman, Ian (Bristol, UK Blue Ridge Summit, PA Channel View Publications, 2020)
"This book offers a critical account of the historical evolution of tourism through the identification and discussion of key turning points. Based on these considerations, future turning points are identified and evaluated. The core findings of the book provide the first perspective on how the history of tourism will shape its future"--
Does the past shape the future? / Ian Yeoman and Una McMahon-Beattie -- History of the future of tourism / Bertus van der Tuuk -- The development of mass tourism / Jim Butcher -- The historical future of tourism : the case of Malta's policies / Marie-Louise Mangion -- Jules Verne as a key to understanding Irish tourism / Klaus Pfatschbacher -- The growth, decline and resurgence of the city-state / Brian Hay -- Geohistorical analysis of costal Tourism in China (1841-2017) / Benjamin Taunay -- The future past of aircraft technology and their impact on stopover destinations / Rafael Castro, Gui Lohmann, Bojana Spasojevic, Carla Fraga and Thiago Allis -- Forever young and new : cruise tourism / Wendy London and Wallace Farias -- From muscles to electrons : a technological look at the futures of energy, transport, and tourism / Jonathan Hui -- Hotel history / Kevin James -- Historical employment relations in the New Zealand tourism hotel sector : from a collective past to an individual future / David Williamson -- Film tourism through the ages : from Lumiére to virtual reality / Peter Bolan and Mihaela Ghisoiu -- The evolution of the Grand Tour in the digital society / Sabrina Seeler -- Shopping on the edge : identifying factors contributing to tourist retail development in heritage villages / Gianna Moscardo, Laurie Murphy, Karen Hughes, Pierre Benckendorff -- Tourism and religion : pilgrims, tourists and travellers : past, present and future / Richard Butler and Wantanee Suntikul -- History and future of mountaineering tourism / Ghazali Musa and Md Moniruzzaman Sarker -- Sustainability, ecotourism and Scotland : concerns, complaints conflicts and conservation / Alastair Durie, Ian Yeoman and Una McMahon-Beattie -- Does the past shape the future of tourism? : a cognitive map(s) perspective / Ian Yeoman and Una McMahon-Beattie.
Includes bibliographical references and index.
Keywords: Hospitality industry -- Forecasting; Hospitality industry -- History; Tourism -- Forecasting; Tourism -- History